Word toys - Stefans, Brian Kim (The University of Alabama Press, 2017)
Introduction: Beyond estrangement – Playing the field: figures toward a speculative prosody – The new commodity: technicity and poetic form – Pilots of the pharmakon: bodies, precarity, and the milieu – Fictions of immanence: undigests and outsider writing – Terrible engines: toward a literature of sets – Miscegenated scripts: the gramme and transpacific hybridity – Discompositions: troubling ground in graphic design – Just ask lattice: a poetics of grids, numbers, and diagrams – Appendix:
Includes bibliographical references and index
Keywords: Literature and technology; Literature; Modern; Digital humanities; Poetics; Digital media; Mass media and technology